Adolescent girls' use of social media for challenging sexualization. (2nd January 2021) - van Oosten, Johanna M. F.
Abstract: Research on sexualized media content has largely neglected an important part of young people's interactions with such content, namely whether and how young people are able to resist sexualization in the media and build resilience against its influence. This study is one of the first to investigate whether adolescent girls build such resilience by reading and sharing messages (e.g., videos, articles) on social media in which sexualization is criticized (i.e., counter-messages). A focus group study of 24 girls aged 12–17, showed that girls engage very little with counter-messages in social media. Explanations for this lack of engagement are related to uses and gratifications of social media (e.g., hedonic and utilitarian value), social influence processes (e.g., identification and compliance with social norms) and media literacy skills (e.g., perceived susceptibility to and awareness of sexualization).